Neuropsychiatric Systemic Lupus Erythematosus Is Dependent on Sphingosine-1-Phosphate Signaling - Mike, Elise V.; Makinde, Hadijat M.; Der, Evan; Stock, Ariel; Gulinello, Maria; Gadhvi, Gaurav T.; Winter, Deborah R.; Cuda, Carla M.; Putterman, Chaim (Frontiers in Immunology, 2018)
About 40% of patients with systemic lupus erythematosus experience diffuse neuropsychiatric manifestations, including impaired cognition and depression. Although the pathogenesis of diffuse neuropsychiatric SLE (NPSLE) is not fully understood, loss of brain barrier integrity, autoreactive antibodies, and pro-inflammatory cytokines are major contributors to disease development. Fingolimod, a sphingosine-1-phosphate (S1P) receptor modulator, prevents lymphocyte egress from lymphoid organs through functional antagonism of S1P receptors. In addition to reducing the circulation of autoreactive lymphocytes, fingolimod has direct neuroprotective effects such as preserving brain barrier integrity and decreasing pro-inflammatory cytokine secretion by astrocytes and microglia. Given these effects, we hypothesized that fingolimod would attenuate neurobehavioral deficits in MRL-lpr/lpr (MRL/lpr) mice, a validated neuropsychiatric lupus model. Fingolimod treatment was initiated after the onset of disease, and mice were assessed for alterations in cognitive function and emotionality. We found that fingolimod significantly attenuated spatial memory deficits and depression-like behavior in MRL/lpr mice. Immunofluorescent staining demonstrated a dramatic lessening of brain T cell and macrophage infiltration, and a significant reduction in cortical leakage of serum albumin, in fingolimod treated mice. Astrocytes and endothelial cells from treated mice exhibited reduced expression of inflammatory genes, while microglia showed differential regulation of key immune pathways. Notably, cytokine levels within the cortex and hippocampus were not appreciably decreased with fingolimod despite the improved neurobehavioral profile. Furthermore, despite a reduction in splenomegaly, lymphadenopathy, and circulating autoantibody titers, IgG deposition within the brain was unaffected by treatment. These findings suggest that fingolimod mediates attenuation of NPSLE through a mechanism that is not dependent on reduction of autoantibodies or cytokines, and highlight modulation of the S1P signaling pathway as a novel therapeutic target in lupus involving the central nervous system.